Artificial neural network-based cooling capacity estimation of various radiator configurations for power transformers operated in ONAN mode - Koca, Aliihsan; Senturk, Oguzkan; Colak, Andac Batur; Bacak, Aykut; Dalkilic, Ahmet Selim (ELSEVIER, 2024)
Power transformers submerged in oil are universally acknowledged as very useful elements in electrical power networks. A fraction of the electrical energy involved in the conversion from high to low voltages is lost as thermal energy, which is produced inside the transformer's windings and core. The effective dissipation of heat is of paramount significance and can be accomplished through the strategic installation of radiators on the tank. This study aims to examine the total cooling capacity of a radiator employed for cooling a power transformer operating in oil, natural air, and natural mode. The investigation is conducted by varying the design parameters, specifically the number of fins per radiator and the radiator length. The study also utilizes computational fluid dynamics results to achieve a substantial convergence with experimental findings. In the context of the verification study conducted for a specific study point, it was found that the simulation outcomes at a mass flow rate of 0.15 kg/s corresponded to about 7.4 % of the experimental results. Additionally, the cooling capacity value obtained was 7.2 %. In the context of machine learning, the performance of the numerical approach was assessed by employing the Bayesian regularization method. The evaluation revealed that the margin of deviation, mean squared error, and coefficient of determination (R2) metrics yielded values of -0.001 %, 1.32E-02, and 0.99930, respectively.
Keywords: Power transformer; Computational fluid dynamics; ONAN; Transformer cooling; Artificial neural network; HOT-SPOT TEMPERATURE; THERMAL PERFORMANCE; PREDICTION; DIRECTION; Thermodynamics; Energy & Fuels; Engineering; Mechanics